Penerapan Teknik Positive Self Talk Terhadap Keterampilan Sosial Siswa Korban Bullying - Anissa Noviani; Bunyamin Maftuh; Dina Siti Logayah (Journal Pendidikan Ilmu Pengetahuan Sosial, 2024)
Every individual has social skills, but the facts on the ground are that there are still many students who commit acts of bullying or deviant behavior. This research aims to test positive self-talk techniques for social skills in students who are victims of bullying. This research uses a quantitative approach with a experimental method. The results of the research show 1) the results of measuring social skills before giving treatment using the positive self talk technique obtained the lowest results in the medium category, meaning that there were still some students whose level of social skills ability was not good because this measurement was still in the recognition process; 2) the results of measuring social skills after giving treatment using the positive self-talk technique obtained the greatest results which were dominated by the very high category, meaning that in this measurement the students' social skills abilities experienced a very good improvement; and 3) the analysis results show that the Sig. (2-tailed) obtained 0.000 < 0.05, meaning Ho is rejected and Ha is accepted. This means that there is a significant difference between the social skills of students who are victims of bullying before and after implementing treatment with positive self-talk techniques.